Penerapan Asas dan Norma Hak Asasi Manusia dalam Undang-Undang Pemberantasan Tindak Pidana Terorisme (The Application of Human Rights Principles and Norm in the Law on Combating Criminal Acts of Terrorism) - Agus Suntoro (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2020)
The upsurge of terror attacks in various regions of Indonesia in 2018, gave rise to the government and parliament effort to immediately revise Law No. 15 of 2003, which was considered inadequate in eradicating criminal acts of terrorism. The awareness of all parties involved ultimately accelerates the dynamics of the legislation process. Finally, on June 21, 2018 President Joko Widodo passed Law No. 5 of 2018 as a stronger basis in eradicating criminal acts of terrorism and seeking to proportionally protect human rights. Against those backgrounds, this study will look at (a) the legislation process in the formation of Law No. 5 of 2018, and (b) review of the practice of human rights principles and norms of Law No. 5 of 2018. This study uses a qualitative method, with descriptive normative presentation. Primary data sources are based on interviews with the Chairperson of the Working Committee of Bill on Terrorism, human rights activists, and government representatives. The results of this study indicate that legally in the legislation process Law No. 5 of 2018 fulfills the established procedures, but the principles and norms of human rights have not become the main reference in the formation of legal material, especially the issue of arrest, detention, the changing from material to formal offences, interception, and inconsistency of criminal justice system through military involvement. Based on this, we need to encourage a limited revision of Law No. 5 of 2018, so that the eradication of terrorism is stronger and human rights principles are respected, as an embodiment of a democratic rule of law. AbstrakPeningkatan aksi teror pada 2018, mendorong pemerintah dan DPR melakukan revisi terhadap UU No. 15 Tahun 2003 yang dinilai tidak cukup memadai dalam pemberantasan tindak pidana terorisme. Kesadaran semua pihak telah mempercepat proses legislasi dan pada 21 Juni 2018 Presiden Joko Widodo mengesahkan UU No. 5 Tahun 2018. UU hasil revisi ini diharapkan lebih memperkokoh dasar pemberantasan tindak pidana terorisme dan melindungi HAM secara lebih proposional. Bertitik tolak pada hal tersebut, kajian ini akan melihat proses legislasi dalam pembentukan UU No. 5 Tahun 2018 dan meninjau penerapan asas dan norma HAM dalam UU No. 5 Tahun 2018. Penelitian ini menggunakan metode kualitatif dengan penyajian deskriptif normatif. Sumber data primer diperoleh melalui wawancara dengan Ketua Panja RUU Terorisme, aktivis HAM, dan perwakilan pemerintah. Hasil kajian menunjukkan, secara legal formal, proses legislasi UU No. 5 Tahun 2018 memenuhi prosedur yang ditetapkan, namun dari aspek substansial masih belum sepenuhnya selaras dengan asas dan norma HAM, terutama persoalan penangkapan, penahanan, perubahan delik materiil menjadi formil, penyadapan, dan inkonsistensi criminal justice system melalui pelibatan militer. Berdasarkan hal tersebut, revisi terbatas terhadap UU No. 5 Tahun 2018 perlu dilakukan agar penegakan hukum pemberantasan terorisme lebih kuat dan HAM dijunjung tinggi sebagai perwujudan negara hukum demokratis.